Hubungan Aspek Fisik Spiritual dan Sosial Anak di Daerah Rawan Bencana dalam Pembelajaran Pendidikan Jasmani dan Olahraga - Yuwono, Pratik Hari; Febrianta, Yudha; Darojat, Darojat; Bintaro, Tri Yuliansyah (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This research originated from the problem that children in disaster-prone areas need improvement and physical, spiritual and social strengthening. This study aimed to evaluate and test the impact of several models of physical education and sports learning in improving the physical, spiritual and social aspects of children in disaster-prone areas. The research was conducted at Kalipagu State Elementary School with 20 students. The research instrument used a questionnaire for data analysis using normality and linearity tests and correlation analysis. Based on the results of data analysis, hypothesis testing and discussion, the results of this study show that the value of Fount between the physical, spiritual, and social aspects of physical learning is 4.112. Meanwhile, the price of Ft (? = 0.05)(3.19) is 3.127. Because the value of Fount is greater than Ftable (Fount> Ftable), the hypothesis that states that there is no jointly significant relationship between the independent and dependent variables is rejected; thus, it can be concluded that together there is an essential relationship between physical, spiritual, and social aspects of biological learning. Keywords: relationship, physical, spiritual, social, physical education